Characterization of methicillin-resistant coagulase-negative Staphylococci Isolates from blood cultures in a Brazilian University Hospital - Pereira, Valeria Cataneli [UNESP] (2011)
Coagulase-negative staphylococci (CNS) are the microorganisms most frequently isolated from clinical materials and represent the leading cause of bacteremia in hospitals. The pathogenesis of infections caused by these bacteria can be aggravated due to antimicrobial resistance and virulence factors. Thus, the present study characterized the CNS species isolated from blood cultures from inpatients of the University Hospital of Botucatu School of Medicine for the detection of methicillin-resistant Staphylococcus (MRS) and staphylococcal enterotoxin genes. The gene mecA was detected in 83.7% CNS and the staphylococcal cassette chromosome mec was typed in MRS, indicating 45.8% type ILI, 25% type I, 11.1% type IV and 5.5% type II. The search for staphylococcal enterotoxin genes indicated that 77 samples were positive for at least one gene. The data obtained in this study highlight the importance of detecting and characterizing MRS and virulence factors to better understand the profile of the isolated CNS in order to appropriately treat infections caused by these microorganisms.